Longitudinal analysis of quality‐of‐life outcomes in children during treatment for acute lymphoblastic leukemia: A report from the Children's Oncology Group AALL0932 trial. Issue 3 (7th November 2017) - Zheng, Daniel J.; Lu, Xiaomin; Schore, Reuven J.; Balsamo, Lyn; Devidas, Meenakshi; Winick, Naomi J.; Raetz, Elizabeth A.; Loh, Mignon L.; Carroll, William L.; Sung, Lillian; Hunger, Stephen P.; Angiolillo, Anne L.; et al.
Abstract : BACKGROUND: Children with average‐risk acute lymphoblastic leukemia (AR‐ALL) face many challenges that can adversely affect their quality of life (QOL). However, to the authors' knowledge, patterns and predictors of QOL impairment during therapy have not been well characterized to date. METHODS: Patients with AR‐ALL who were enrolled on the Children's Oncology Group AALL0932 trial were offered participation in this prospective cohort study if they were aged ≥4 years at the time of diagnosis and had an English‐speaking parent. At approximately 2 months, 8 months, 17 months, 26 months, and 38 months (boys only) after diagnosis, parents completed the Pediatric Quality of Life Inventory Generic Core Scales Version 4.0 (PedsQL4.0) and McMaster Family Assessment Device instruments for QOL (physical, emotional, and social functioning) and family functioning, respectively. The proportions of individuals scoring in the impaired range (2 standard deviations below the population mean) were calculated at each time point. Longitudinal impairment patterns and predictors were examined. RESULTS: A total of 594 participants with AR‐ALL were diagnosed at a mean age of 6.0 years (standard deviation, 1.6 years). At 2 months, a substantial proportion of participants had impaired scores for physical (36.5%; 95% confidence interval [95% CI], 32.3%‐40.8%) and emotional (26.2%; 95% CI, 22.5%‐30.2%) functioning compared with population norms of 2.3%. These elevations persisted at 26 months. Emotional impairment at 2 months (odds ratio, 3.4; 95% CI, 1.5‐7.7) was found to significantly predict emotional impairment at 26 months. In repeated measures analysis with multivariate modeling, unhealthy family functioning (odds ratio, 1.5; 95% CI, 1.1‐2.1) significantly predicted emotional impairment controlling for age and sex. QOL outcomes were similar between sexes at the end of therapy (26 months for girls and 38 months for boys). CONCLUSIONS: Many children with AR‐ALL experience physical and emotional functioning impairment that begins early in treatment and persists. Early screening may identify high‐risk patients who might benefit from family‐based interventions. Cancer 2018;124:571‐9. © 2017 American Cancer Society . Abstract : Many children with average‐risk acute lymphoblastic leukemia experience substantial impairments in both physical and emotional functioning that begin early in treatment and persist. Early screening for quality‐of‐life impairment and poor family functioning may identify high‐risk patients for intervention.